An Analysis of Brainstorming Learning Strategy on the Students’ Writing Descriptive Text in Junior High School - Farida Repelita Waty Kembaren; Indi Vira Patmala (Institut Agama Islam Negeri Palopo, 2022)
This study was conducted to analyze how the brainstorming learning strategy on students in writing descriptive text with the aim of describing how the brainstorming learning strategy on students in writing descriptive text. This study uses a case study in qualitative research. The participants in this study were students of grade 8-b MTs Munawwarah Amal Bhakti Kec. Ujung Padang Kab. Simalungun, totaling 26 students consisting of 16 male students and 10 female students. Data collection was carried out using class observation, interviews with teachers and students and documentation. The findings of this study state that the brainstorming learning strategy in writing descriptive text for grade 8-b students makes students actively think to express their opinions through writing, Students can learn to think quickly and, Students feel comfortable and satisfied, Teach students to be disciplined, Increase vocabulary understanding in English. Based on the findings, the researcher gives suggestions as teachers should continue to apply brainstorming learning strategies in writing descriptive text, because in addition to training students to write, they also train students to think. Teachers can use audio-visual media such as in focus in explaining learning materials so that learning is more interesting. Teachers should require students to bring a dictionary in English lessons, in order to improve vocabulary comprehension. Schools must provide or facilitate media in teaching, so that learning becomes interesting and students can understand the lesson well.